Liposomes as nanomedical devices - Bozzuto G (Dove Medical Press, 2015)
Giuseppina Bozzuto,1,2 Agnese Molinari2 1Chemical Methodology Institute, CNR, 2Department of Technology and Health, Istituto Superiore di Sanità, Rome, Italy Abstract: Since their discovery in the 1960s, liposomes have been studied in depth, and they continue to constitute a field of intense research. Liposomes are valued for their biological and technological advantages, and are considered to be the most successful drug-carrier system known to date. Notable progress has been made, and several biomedical applications of liposomes are either in clinical trials, are about to be put on the market, or have already been approved for public use. In this review, we briefly analyze how the efficacy of liposomes depends on the nature of their components and their size, surface charge, and lipidic organization. Moreover, we discuss the influence of the physicochemical properties of liposomes on their interaction with cells, half-life, ability to enter tissues, and final fate in vivo. Finally, we describe some strategies developed to overcome limitations of the “first-generation” liposomes, and liposome-based drugs on the market and in clinical trials. Keywords: liposomes, nanomedicine, drug delivery, ultrastructure